2017
DOI: 10.1007/s10750-017-3276-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific turnover rates of the nitrogen stable isotope as functions of time and growth in a cyprinid fish

Abstract: Ecological applications of stable isotope data require knowledge on the isotopic turnover rate of tissues, usually described as the isotopic half-life in days (T 0.5 ) or the change in mass (G 0.5 ). Ecological studies increasingly analyse tissues collected nondestructively, such as fish fin and scales, but there is limited knowledge on their turnover rates. Determining turnover rates in situ is challenging, with ex situ approaches preferred. Correspondingly, T 0.5 and G 0.5 of the nitrogen stable isotope (d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…For example, Heady and Moore calculated half‐lives for muscle, fin and scales in rainbow trout ( Oncorynchus mykiss ) and found that fin had the shortest δ 15 N half‐life (13 days), followed by muscle (39 days). In contrast, a study on juvenile barbel ( Barbus barbus ) found δ 15 N half‐lives to be longer in fin tissue (95 days) and shorter in muscle tissue (84 days) . Other studies have reported similar turnover rates for fin and muscle tissues .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Heady and Moore calculated half‐lives for muscle, fin and scales in rainbow trout ( Oncorynchus mykiss ) and found that fin had the shortest δ 15 N half‐life (13 days), followed by muscle (39 days). In contrast, a study on juvenile barbel ( Barbus barbus ) found δ 15 N half‐lives to be longer in fin tissue (95 days) and shorter in muscle tissue (84 days) . Other studies have reported similar turnover rates for fin and muscle tissues .…”
Section: Discussionmentioning
confidence: 91%
“…For example, the fin‐muscle relationship has been shown to vary with the diet type, tissue type and size of the fish . These differences are likely to be most pronounced for species that either have a wide prey range, such as omnivores or that are likely to experience seasonal variation in prey availability . In other studies, correction models for converting fin isotope ratios into muscle isotope ratios have been used, and, in some cases, they are species‐specific or population‐specific .…”
Section: Introductionmentioning
confidence: 99%
“…As the adonis function is similar to traditional ANOVA, it provided a pseudo F-statistic and P value based on 999 permutations of the data (Dixon, 2003 To compare 'core' trophic niche size and overlaps within and between species, the isotopic niche was used, where the isotopic niche is an approximation of the trophic niche. It is acknowledged that the isotopic niche varies slightly from the trophic niche due to it being influenced by factors other than diet (Jackson et al, 2011), such as growth and metabolic rate of individuals (Busst & Britton, 2017). It was calculated using the metric 'standard ellipse area' (SEA), a bivariate measure of the distribution of individuals in isotopic space (Jackson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…δ 13 C and δ 15 N), as this can provide a temporally integrated assessment of diet (Cucherousset, Boulêtreau, Martino, Roussel & Santoul, 2012). This will, however, mean that the experiment will need to be of sufficient duration for sufficient isotopic turnover in the tissues to ensure the SI data reflects the diet of the fishes within the mesocosms/ ponds and not their previous diets (Busst and Britton, 2018). Where assessments of impacts on zooplankton communities or decomposition rates are required, experimental length can be shorter, with the application of, for example, 'leaf packs' for assessing cascading impacts on decomposition rates (Jackson, Ruiz-Navarro & Britton, 2015).…”
Section: Mesocosm and Pond Experimentsmentioning
confidence: 99%